2013
DOI: 10.1371/journal.pone.0066809
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and piRNA Profiles in Normal Human Testis Detected by Next Generation Sequencing

Abstract: BackgroundMicroRNAs (miRNAs) are the class of small endogenous RNAs that play an important regulatory role in cells by negatively affecting gene expression at transcriptional and post-transcriptional levels. There have been extensive studies aiming to discover miRNAs and to analyze their functions in the cells from a variety of species. However, there are no published studies of miRNA profiles in human testis using next generation sequencing (NGS) technology.ResultsWe employed Solexa sequencing technology to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 77 publications
(65 reference statements)
8
83
1
1
Order By: Relevance
“…Next generation sequencing analysis of short RNA transcriptome from testes of three normal men identified 775 miRNAs and 20121 piRNAs, indicating the abundance and complexity of short non-coding RNAs in the human testis [112]. The most abundant miRNAs detected in this study were let-7 family members, miR-34c-5p, miR-103a-3p (meaning a part from the 3' arm), miR-202-5p, miR-508-3p, and miR-509-3-5p, which target gene transcripts involved in regulation of meiosis, spermatogenesis, germ cell apoptosis, testicular development, p53-related pathways, and homologous recombination pathways [112].…”
Section: Role Of Protamination In Male Infertilitymentioning
confidence: 99%
“…Next generation sequencing analysis of short RNA transcriptome from testes of three normal men identified 775 miRNAs and 20121 piRNAs, indicating the abundance and complexity of short non-coding RNAs in the human testis [112]. The most abundant miRNAs detected in this study were let-7 family members, miR-34c-5p, miR-103a-3p (meaning a part from the 3' arm), miR-202-5p, miR-508-3p, and miR-509-3-5p, which target gene transcripts involved in regulation of meiosis, spermatogenesis, germ cell apoptosis, testicular development, p53-related pathways, and homologous recombination pathways [112].…”
Section: Role Of Protamination In Male Infertilitymentioning
confidence: 99%
“…Though earlier work established that piRNA pathway features are conserved between humans and other mammals (Aravin et al 2006;Girard et al 2006;Yang et al 2013;Ha et al 2014;Roovers et al 2015;Rosenkranz et al 2015a;Rounge et al 2015;Williams et al 2015), due to ethical and technical limitations, research progress in humans has been slower. Specifically, while all postnatal human piRNAs were previously mapped to piRNA clusters (Ha et al 2014;Roovers et al 2015;Rosenkranz et al 2015a;Williams et al 2015), these clusters were ill-defined in the genome.…”
Section: Introductionmentioning
confidence: 99%
“…Walter et al [43] analyzed 86 adult AML cases using ultra-high resolution Affymetrix 6.0 SNP arrays with paired normal DNA in all cases, whereas Radtke et al [44] studied 111 pediatric AML cases with high-resolution SNP arrays (combination of 100K and 500K arrays) using paired samples for 65 patients and higher stringency criteria to define abnormalities for the remaining 46 patients. The studies identified only 12 or 18 regions with significantly recurrent chromosome number abnormalities (CNAs), respectively, and an average of 2.3 CNAs/AML genome [45,46]. Thus, given the low frequency of recurring CNAs in AML compared with other cancers, it becomes critically important to discriminate between true acquired CNAs and inherited chromosome number variations (CNVs).…”
Section: Single Nucleotide Polymorphism Arraymentioning
confidence: 99%
“…For example, exome sequencing is a technique in which only the coding regions of the genome are sequenced [45], allowing for selective capture of the genomic regions of interest from a DNA sample prior to sequencing. It is also possible to select small RNAs using size selection, or similar capture strategies as described above, to perform comprehensive small RNA profiling in patient samples [46]. Another popular technique is the whole transcriptome sequencing or RNA-Seq, where all RNA species, including total RNA and small RNA, are sequenced [47].…”
Section: Whole Genome Sequencingmentioning
confidence: 99%